2018
DOI: 10.1103/physrevb.97.115160
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for momentum-dependent heavy-fermionic electronic structures: Soft x-ray ARPES for the superconductor CeNi2Ge2 in the normal state

Abstract: We present clear experimental evidence for the momentum-dependent heavy fermionic electronic structures of the 4f -based strongly correlated system CeNi 2 Ge 2 by soft x-ray angle-resolved photoemission spectroscopy. A comparison between the experimental three-dimensional quasiparticle dispersion of LaNi 2 Ge 2 and CeNi 2 Ge 2 has revealed that heavy fermionic electronic structures are seen in the region surrounding a specific momentum. Furthermore, the wave vectors between the observed "heavy spots" are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
(68 reference statements)
2
4
0
Order By: Relevance
“…This result suggests that the change in the electronic structure starts at a much higher temperature than T K . A similar thermal effect in the σ(ω) spectra has been reported from ARPES results of CeNi 2 Ge 2 [7], YbRh 2 Si 2 [43], and CeCoIn 5 [11].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result suggests that the change in the electronic structure starts at a much higher temperature than T K . A similar thermal effect in the σ(ω) spectra has been reported from ARPES results of CeNi 2 Ge 2 [7], YbRh 2 Si 2 [43], and CeCoIn 5 [11].…”
Section: Discussionsupporting
confidence: 83%
“…Since the effective carrier mass can be described as m * = kdk/dE(k)| k=k F of the dispersion curve of the conduction band E(k), where k is the wavenumber, the band dispersion is expected to be modified with temperature. Whereas the change of the density of states of the conduction band is contained in the optical conductivity (σ(ω)) and scanning tunneling spectroscopy measurements [2], the band dispersions E(k) can be directly detected by angle-resolved photoelectron spectroscopy (ARPES), which is a method now being widely used in HF materials [3,4,5,6,7]. However, since ARPES is very sensitive to solid surfaces due to low-energy electrons' detection, the results are sometimes inconsistent with bulk properties such as transport.…”
Section: Introductionmentioning
confidence: 99%
“…Since the effective carrier mass can be described as m * = k dk/dE(k)| k=k F of the dispersion curve of the conduction band E(k), where k is the wavenumber, the band dispersion is expected to be modified with temperature. Whereas the change of the density of states of the conduction band is contained in the optical conductivity (σ(ω)) and scanning tunneling spectroscopy measurements [2], the band dispersions E(k) can be directly detected by angle-resolved photoelectron spectroscopy (ARPES), which is a method now being widely used in HF materials [3][4][5][6][7]. However, since ARPES is very sensitive to solid surfaces due to low-energy electrons' detection, the results are sometimes inconsistent with bulk properties such as transport.…”
Section: Introductionmentioning
confidence: 99%
“…Later, it was observed that the Kondo peak is intensive at Fermi vectors [8]. Finally, it was shown that bands, which are strongly correlated with 4f electrons, coexist with those weakly correlated within a single heavy fermion system [9] and that hybridization changes with momentum [10]. In fact, anisotropic structure of V cf is a source of a Kondo resonance intensity variation along the Fermi surface (FS), which is due to a particular distribution of f-electron density in reciprocal space.…”
Section: Introductionmentioning
confidence: 99%